Structural and Magnetic Properties of Microwave Assisted Sol-Gel Synthesized La0.9Sr0.1MnO3 Manganite Nanoparticles. (10th February 2014) - Eshraghi, Mahin; Kameli, Parviz
Abstract : The structural and magnetic properties of nanoparticles of La 0 .9 Sr 0 .1 MnO 3 (LSMO) were studied using powder X-ray diffraction (XRD), transmission electron microscope (TEM), and magnetic measurements. The XRD refinement result indicates that samples crystallize in the rhombohedral structure with R-3C space group. The dc magnetization measurements revealed that samples exhibit no hysteretic behavior at room temperature, symptomatic of the superparamagnetic (SPM) behavior. The results of ac magnetic susceptibility measurements show that the susceptibility data are not in accordance with the Néel-Brown model for SPM relaxation but fit well with conventional critical slowing down model which indicates that the dipole-dipole interactions are strong enough to cause superspin-glass-like phase in LSMO samples.